CEPHALOMETRIC RADIOGRAPH DESCRIPTION OF PHARYNGEAL AIRWAYAND HYOID BONE POSITION IN CLASS I AND CLASS II SKELETAL MALOCCLUSION SUBJECT - Rosdiana, Nova (Cakradonya Dental Journal, 2021)
The width of pharyngeal airway can be affected by skeletal pattern and hyoid bone position. The purpose of this study was to analyze the difference between upper and lower pharyngeal airway and hyoid bone position in class I and II skeletal malocclusion patients using cephalometric. The descriptive analytical study design was used to analyse the secondary data collected from patients in Dental Radiology installation, RSGM UNPAD. Sample size was determined using purposive sampling method with the total of 44 cephalometric. The average of upper pharyngeal airway width in class I was 14,814,08 mm and 12,273,16 mm in class II with P value of 0,0026 (P 0,05). The average of lower pharyngeal airway width in class I was 11,662,57 mm and 10,621,77 mm in class II with P Value of 0,202 (P0,05). The hyoid bone position revealed similar results between class I and II malocclusions showing that 7 subjects had positive triangle positions and 15 patients had negative triangle positions with P value of 1,000 (P0,05). The difference of upper pharyngeal airway width between class I and II skeletal malocclusion patients was considered significant. In contrary, there was no significant difference found in lower pharyngeal airway and hyoid bone position.